High-efficiency fullerene solar cells enabled by a spontaneously formed mesostructured CuSCN-nanowire heterointerface - Sit, W; Eisner, F; Lin, Y; Firdaus, Y; Seitkhan, A; Balawi, A; Laquai, F; Burgess, C; Mclachlan, M; Volonakis, G; Giustino, F; Anthopoulos, T (Wiley, 2018)
Fullerenes and their derivatives are widely used as electron acceptors in bulk-heterojunction organic solar cells as they combine high electron mobility with good solubility and miscibility with relevant semiconducting polymers. However, studies on the use of fullerenes as the sole photogeneration and charge-carrier material are scarce. Here, a new type of solution-processed small-molecule solar cell based on the two most commonly used methanofullerenes, namely [6,6]-phenyl-C61-butyric acid methyl ester (PC 60 BM) and [6,6]-phenyl-C71-butyric acid methyl ester (PC 70 BM), as the light absorbing materials, is reported. First, it is shown that both fullerene derivatives exhibit excellent ambipolar charge transport with balanced hole and electron mobilities. When the two derivatives are spin-coated over the wide bandgap p-type semiconductor copper (I) thiocyanate (CuSCN), cells with power conversion efficiency (PCE) of ≈1%, are obtained. Blending the CuSCN with PC 70 BM is shown to increase the performance further yielding cells with an open-circuit voltage of ≈0.93 V and a PCE of 5.4%. Microstructural analysis reveals that the key to this success is the spontaneous formation of a unique mesostructured p-n-like heterointerface between CuSCN and PC 70 BM. The findings pave the way to an exciting new class of single photoactive material based solar cells.